Knowledge flows, governance and the multinational enterprise : - Mahnke, Volker (Palgrave Macmillan, 2004)
The book contributes to the understanding of knowledge governance in the multinational corporation (MNC). It is concerned with the attraction of crucial capital, its efficient allocation, as well as the mechanisms used to achieve capital accumulation and optimal utilization. However, unlike the traditional literature, this book does not concentrate on financial capital, but on knowledge as a particular sort of capital that is seen as increasingly crucial to the existence, boundaries and economic organization of the modern MNC.